An econometric assessment of the change in quality of the Irish gilt market since the introduction of market making - Dunne, Peter G. (Economic & Social Studies, 1996)
Hasbrouck's (1993) measure of market quality is used to assess the effect of introducing market making in Irish Gilts. The measure is based on aspects of the literature on the decomposition of time series' into stochastic trend and stationary components. The Hasbrouck approach is modified somewhat, first, to account for a trade-type indicator in a different way than before, and second, by allowing for time variation in the variance of the relevant components. A measure for comparison of different market regimes is obtained and on the basis of this measure the Irish Gilt market appears to be quite competitive at present.
Keywords: Gilts; Money market; Econometric modelling; Ireland